Theme in conversational discourse : problems experienced by speakers of Black South African English, with particular reference to the role of prosody in conversational synchrony - Gennrich-de Lisle, Daniela (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1986)
This study is an investigation of instances of conversational failure in interaction as evidenced by speakers of Black South African English (BSAE) , with a particular focus on the role of prosody in conversational (a)synchrony. The data analysed consist of six conversations, one SAE-SAE (South African English) encounter, four BSAE- SAE encounters and one BSAE- BSAE encounter. After a theoretical framework is set up, the analysis is conducted by means of two triangulation research processes based on Ethnomethodology. The analysis consists of an investigation into selected extracts which participants and informants alike perceived as 'stressful'. An attempt is made to isolate the sources of each instance of pragmatic failure. Prosodic features are found to be important in establishing and maintaining theme and conversational synchrony. But other factors are also involved. The analysis reveals two major influences of asynchrony: deviance in the use of (in order of importance) prosodic, lexical and syntactic cues to discourse functions; and a mismatch in the application of socio-cultural principles guiding conversational behaviour. The study leads into a brief outline of aims, objectives and conversational competence at a tertiary level and concludes with suggestions for further research.
Keywords: English language -- Spoken English -- Foreign speakers; Black English -- South Africa